Customers’ Prior Knowledge in the Servitization of Traditional Handicrafts - Bach Q. Ho (Businesses, 2024)
To enhance the competitiveness of the traditional handicraft industry, providers should offer service experiences using their products (i.e., servitization) instead of merely selling them. Effective management for servitization in the traditional handicraft industry must consider the differences in customers’ prior knowledge. Nevertheless, previous studies have overlooked how this knowledge about traditional handicrafts impacts service experiences. This study explores which factors of consumer behavior (during services) and service outcomes (post-services) are affected by customers’ prior knowledge about a traditional handicraft. An organic food restaurant booth was provided at an annual summer festival about pottery as an experiment, and data were collected on customers’ meal experiences with a pottery plate through a questionnaire. The findings suggest that customers’ prior knowledge about a traditional handicraft promotes their search for information from service resources (i.e., organic foods) which are integrated with the traditional handicraft and their creativity during services, thereby changing their understanding of service resources and increasing satisfaction with service experience. This study contributes to services marketing by identifying the factors of during and post-services that are affected by customers’ prior knowledge about a traditional handicraft in the context of servitization.